2020
DOI: 10.1002/cam4.2966
|View full text |Cite
|
Sign up to set email alerts
|

Once‐a‐week or every‐other‐day urethra‐sparing prostate cancer stereotactic body radiotherapy, a randomized phase II trial: 18 months follow‐up results

Abstract: Background:To present the 18 months results from a prospective multicenter phase II randomized trial of short vs protracted urethra-sparing stereotactic body radiotherapy (SBRT) for localized prostate cancer (PCa). Methods: Between 2012 and 2015, a total of 170 PCa patients were randomized to 36.25 Gy in 5 fractions (6.5 Gy × 5 to the urethra) delivered either every other day (EOD, arm A, n = 84) or once a week (QW, arm B, n = 86). Genitourinary (GU) and gastrointestinal (GI) toxicity (CTCAE v4.0 scale), IPSS,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…Patients in the experimental arm were treated with 7 × 6.1 Gy to the prostate without the seminal vesicles, whereby roughly ¾ of patients were treated with 3D-conformal RT (3DCRT). Zilli and colleagues conducted a phase II trial investigating urethra-sparing SBRT with treatment once a week vs. every other day with a prescription dose of 5 × 7.25 Gy to the prostate ± the seminal vesicles [ 58 ]. King et al [ 29 ] reported on pooled phase II data of a multi-institutional consortium.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients in the experimental arm were treated with 7 × 6.1 Gy to the prostate without the seminal vesicles, whereby roughly ¾ of patients were treated with 3D-conformal RT (3DCRT). Zilli and colleagues conducted a phase II trial investigating urethra-sparing SBRT with treatment once a week vs. every other day with a prescription dose of 5 × 7.25 Gy to the prostate ± the seminal vesicles [ 58 ]. King et al [ 29 ] reported on pooled phase II data of a multi-institutional consortium.…”
Section: Resultsmentioning
confidence: 99%
“…In the phase II trial conducted by Zilli and colleagues, a 6-month LHRHa treatment (2 months neoadjuvant) was mandatory in all patients with HR features [ 58 ]. In the US multi-institutional phase II series, 38% of the HR PCA patients underwent short-course neoadjuvant and concurrent ADT for a median duration of 4 months [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These are likely driven by radiation dose delivered to critical adjacent normal tissue. Aggressive urethral sparing in CT-guided SBRT has shown a considerable reduction in acute GU toxicity demonstrated by Zilli et al [ 35 ]; however, certain key features of this practice such as routine use of a Foley catheter and endorectal balloon may limit the widespread adoption. The dose in that study (36.25Gy in 5 fractions) is also lower than in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Urethra sparing is performed in SBRT and brachytherapy, since higher urethral doses are associated with higher GU toxicities (59,60). The recently published toxicity reports of the hypoFlame trial suggest that prioritization of OAR constraints yields acceptable toxicities for focal dose escalation using SBRT.…”
Section: Discussionmentioning
confidence: 99%